Statistical modeling in teacher education (2023)
ABSTRACT: The purpose of this research is to investigate prospective teachers’ learning in the statistical modeling process. To reach this goal, we position the study in a socio-critical perspective of modeling that informed the design of a statistical investigation. Participants were 10 prospective teachers from a state university in northwestern Colombia who were taking a methods course in statistics. They worked out a statistical investigation inspired by a news article on global warming. The main source of data was fragments from prospective teachers’ speech while working out the statistical investigation. The information was complemented with prospective teachers’ narratives in which they reflected on their experience with statistics. The results reveal that the prospective teachers’ discourse offers indications to suggest that the participants were in the process of developing statistical knowledge as well as developing awareness as critical citizens. Prospective teachers used statistics tools to (1) make sense of a crisis of society while progressing in the development of their statistical knowledge and (2) reflect on the critical issue while showing signs of social awareness development.